Affirmative action and private education expenditure by disadvantaged groups: Evidence from India - Athira Vinod (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2024)
Under the Right to Education Act (2009), the Indian government introduced a policy that required private schools to reserve 25% of primary school places for children from socially disadvantaged households. This paper examines the impact of the RTE Act's reservation policy on private school expenditure by socially disadvantaged households. Leveraging the age of school entry and using a difference-in-difference approach, this paper finds a significant decrease in private school fees for disadvantaged children postpolicy. This reduction is more pronounced in districts with higher enrolment rates under the policy. The change is attributed to a rise in low-cost private schools post-policy, facilitating cheaper education for disadvantaged students. Moreover, there exists a strong correlation between the growth of low-cost schools and increased policy enrolments at the district level.
Keywords: I21; I22; I24; I28; 330; Private schools; Disadvantaged groups; Right to Education Act; Reservation policy